Differential clinical presentation of Adamantiades–Behçet's disease in non‐endemic and endemic areas: retrospective data from a Middle‐European cohort study. (17th April 2018) - Moosmann, Thomas; Veraar, Cécilia; Brunner, Jürgen; Fraedrich, Gustav; Frech, Andreas; Horninger, Wolfgang; Ratzinger, Gudrun; Streif, Werner; Teuchner, Barbara; Willeit, Johann; Zlamy, Manuela; De Zordo, Tobias; et al.
Abstract: Objectives: To assess demographical and clinical data in a Middle‐European cohort of patients with Adamantiades–Behçet's disease (ABD), together with the use of medication in adherence to international guidelines. Methods: In a retrospective cohort study, in‐ and outpatients of an Austrian secondary and tertiary university hospital center were analyzed independent from the medical discipline involved. After ethics approval, screening for ABD‐patients in the clinical information system resulted in 1821 documents from 1997 to 2016. Patients fulfilling the International Criteria for Behçet's Disease were included, and ABD symptoms and signs together with medical interventions for immunosuppression, anticoagulation and pain management were identified by individual chart reviews and evaluated for conformity with international recommendations. Results: A total of 76 ABD patients were identified with 39.1% Austrian and 37.0% Turkish origin. Genital aphthae and skin manifestations were more frequent, neurological, gastrointestinal and vascular manifestations less frequent in ABD patients of Turkish origin living in Austria compared to those living in Turkey (each P  < 0.05). The male‐to‐female ratio averaged 0.86 (0.39 in patients with Austrian and 1.43 with Turkish backgrounds), and was 3.3 in patients with venous manifestations. Out of 174 medical interventions, 55.2% fully matched the European League Against Rheumatism recommendations of 2008, and 93.7% were considered at least as equal to the recommendations. Indications for tumor necrosis factor inhibition were in line with the 2007 Sfikakis recommendations. Conclusions: In this Middle‐European ABD cohort clinical presentations between patients of Austrian and Turkish origin do not strongly vary, whereas Turkish patients from the non‐endemic Innsbruck cohort present differently compared to patients living in Turkey. The role of such cohort analyses will increase, from the epidemiological as well as the management perspective.